The role of general practitioners in the continued success of the National Cervical Screening Program - Munro, A.; Pavicic, H.; Leung, Y.; Westoby, V.; Steel, N.; Semmens, James; O'Leary, Peter (The Royal Australian College of General Practitioners, 2014)
Background: As the gateway to healthcare for Australian women, general practitioners (GPs) are critical to the success of the National Cervical Screening Program (NCSP). Despite an enviable record – halving the incidence and mortality of cervical cancer – in 2010–2011 more than 2.7 million women did not comply with the recommended 2-yearly screening interval. Objective: General practice strategies are presented to assist GPs in encouraging all women, in particular, high-risk and vulnerable women, to participate in cervical screening. Discussion: GPs play a crucial part in addressing the demographic, psychosocial and healthcare barriers that prevent women’s participation in cervical screening. Encouraging uptake of the human papillomavirus vaccine and educating all patients on the importance of continued participation in cervical screening is essential for further decreasing the prevalence of this disease through early detection and treatment of cervical abnormalities.